Theft, Vandalism, and Other Related Crime in the Beekeeping Industry: A Guide for Beekeepers - Catherine M. Zettel Nalen; James D. Ellis (EDIS, 2010)
ENY157, a 2-page fact sheet by C.M. Zettel Nalen and J.D. Ellis, provides recommendations for crime prevention in beekeeping operations, what to do if hives or equipment are stolen or vandalized, and resources for beekeepers. Published by the UF Department of Entomology and Nematology, September 2010.